Accounting for ourselves and others: Living psychosocial hauntologies - Phoenix, Ann (PINS-Psychology in Society, 2024)
Bhekizizwe Peterson’s interdisciplinarity was wide ranging and displayed his easy familiarity with the Arts, Social Sciences and Philosophy. The breadth of his interests and oeuvre make him genuinely psychosocial, interested, for example, in psychoanalytic issues of mourning and melancholia and bringing this together with deep understandings of narratives and the ways in which the archive demonstrates that assumptions of intergenerational ruptures are overblown since, for example, mourning, melancholia and the rewriting of the archive was a feature of pre-1994 Black South Africa so that pre-1994 has left a wake in the present and for the future. This article takes up Bhekizizwe’s focus on haunting byconsidering how people position themselves in psychosocial, intersectional histories. provoked by everyday subjection to racism. It analyses ‘found narratives’, traces of particular people and/or groups, captured in, for example, filmed documentaries or social media as well as media interviews. It argues that their accounts of everyday subjection to racism are linked to psychosocial, intersectional histories in ways that demonstrate the importance of recognising that unacknowledged histories of racism haunt the present, reproducing the dehumanizing of groups subjected to racism and potentially spurring those affected to consciousness and calls for political action.